Patient‐Reported Symptoms in the Global Multiple System Atrophy Registry. Issue 7 (29th August 2022) - Palma, Jose‐Alberto; Krismer, Florian; Meissner, Wassilios G.; Kuijpers, Mechteld; Millar‐Vernetti, Patricio; Perez, Miguel A.; Fanciulli, Alessandra; Norcliffe‐Kaufmann, Lucy; Bower, Pam; Wenning, Gregor K.; Kaufmann, Horacio
ABSTRACT: Background: The Global Multiple System Atrophy Registry (GLOMSAR) was established in 2013. It is an online patient‐reported contact registry open and free that relies on self‐reported diagnosis by the patient or caregiver. Objectives: To report the demographics of patients enrolled in GLOMSAR and the results of an ancillary online symptom questionnaire. Methods: Patients enrolled in GLOMSAR were invited to complete a custom‐designed online questionnaire about disease onset and symptom prevalence. Results: At the time of writing, there were 1083 participants in GLOMSAR, of which 33% (365) completed the questionnaire. The onset and frequency of most symptoms was similar to those reported in the literature in physician‐reported studies. Some were understudied or not typically associated with multiple system atrophy (MSA), including reduced female sexual sensation (55%), forgetfulness (60%), pseudobulbar affect (37%), olfactory changes (36%), and visual hallucinations (21%). Conclusions: Patient‐reported studies and ancillary online questionnaires are valid, underused research tools useful to advance our knowledge on understudied MSA features and highlight the patients' voice.